SHARIA MUTUAL FUNDS PERFORMANCE IN INDONESIA: ANALYSIS OF THE CAPABILITY OF INVESTMENT MANAGERS WITH THE TREYNOR-MAZUY CONDITION METHOD OF 2016-2018 - Katrina Wigusniarto (UIN Mataram, 2020)
This study aims to test the ability of investment managers in stock selection and market timing, using the Treynor-Mazuy Condition method by adding variables such as exchange rates and inflation as an illustration of investment managers in calculating the systemic risk factors that occur in a country to the performance of Islamic Sharia Mutual Funds in Indonesia in 2016 to 2018. The technique of selecting samples using purposive sampling. Thus, a research sample of 24 Sharia Mutual Fund Products was obtained. Data analysis techniques using panel data regression test with the help of Software Eviews 10 and Microsoft Excel. The results showed that the ability of investment managers in terms of considering the decision to allocate their portfolio of securities based on stock selection affects the performance of Islamic mutual fund shares. Meanwhile, the ability of investment managers in terms of considering the decision to allocate their portfolio of securities based on market timing of the Treynor-Mazuy Condition regression results does not affect the performance of Islamic mutual fund shares. Likewise, the ability of investment managers to consider the decision to allocate portfolio of securities based on systemic risks such as exchange rates and inflation from the Treynor-Mazuy Condition regression results does not affect the performance of Islamic mutual fund shares.